2002
DOI: 10.1016/s0002-9440(10)64894-8
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter bilis Infection Accelerates and H. hepaticus Infection Delays the Development of Colitis in Multiple Drug Resistance-Deficient (mdr1a−/−) Mice

Abstract: mdr1a-deficient mice lack P-glycoprotein and spontaneously develop colitis with age. Helicobacter spp. are gram-negative organisms that have been associated with colitis in certain mouse strains, but Helicobacter spp. have been excluded as contributing to the spontaneous colitis that develops in mdr1a-/- mice. We wished to determine whether infection with either H. bilis or H. hepaticus would accelerate the development of inflammatory bowel disease (IBD) in mdr1a-/- mice. We found that H. bilis infection induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
125
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 56 publications
10
125
0
Order By: Relevance
“…They also indicated that infection with Helicobacter bilis induced diarrhea, weight loss, and IBDs in mdr1a-/-knockout mice. [14][15][16] Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD. 18) Next, MDR1 is located on chromosome 7 at q21.1, 19) which was one of the loci of susceptibility to…”
supporting
confidence: 64%
See 2 more Smart Citations
“…They also indicated that infection with Helicobacter bilis induced diarrhea, weight loss, and IBDs in mdr1a-/-knockout mice. [14][15][16] Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD. 18) Next, MDR1 is located on chromosome 7 at q21.1, 19) which was one of the loci of susceptibility to…”
supporting
confidence: 64%
“…14-16) Macroscopic, microscopic and biochemical examinations have confirmed that the colitis which develops in this model is similar to that of human IBDs, [14][15][16][17] and very recently, it has been confirmed that MDR1 mRNA expression in colonic tissues is down-regulated in patients with UC, but not with CD.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Infection with 1 virus or bacterial species may alter the outcome of infection with another virus or bacterial species. 22,65,74 In this review, we provide a glossary of terms related to GEM, their microbes, and microbial status specifically (Table 1). Although most of these terms will be familiar to readers, certain concepts such as the different definitions of specific pathogen free between facilities, germ free, defined flora, and conventional mice are important to understand.…”
Section: Surveillancementioning
confidence: 99%
“…Helicobacter hepaticus induces hepatitis and hepatocellular carcinoma in the liver in A/JCr mice; causes chronic intestinal inflammation in A/JCr, germfree Swiss Webster mice and immunodeficient mice; H.hepaticus also leads to IBD, associated colon cancer in immune-dysregulated mice (1). Helicobacter bilis is associated with hepatitis in aged inbred and outbred mice; caused IBD and colon cancer in severe combined immunodeficient mice multiple-drug resistance-deficient mice, and WASP-deficient mice and increases the susceptibility for gall stone formation in C57L/J mice (2)(3)(4)(5)(6). Several novel EHS have been reported in recent years.…”
Section: Introductionmentioning
confidence: 99%